The methane adsorption characteristics of marine shale. (2nd September 2017) - Gu, Yang; Ding, Wenlong; Liu, Jingshou; Xiao, Zikang; Lin, Changcheng
ABSTRACT: The marine shale gas in South China has great exploration potential, and exploration in the Sichuan Basin has been successful, but the degree of exploration is low in Guizhou Province. We used organic geochemical analyses, X-ray diffraction (XRD) analysis, and CH4 adsorption experimental methods to study pore structures and their effects on the methane adsorption capacity of organic-rich shales. According to the measured isothermal adsorption data, and based on the theory of adsorption potential, the calculation model of shale adsorption gas under the influence of temperature and pressure is established, and the model is validated and applied by the measured isothermal adsorption data. The results show that the adsorption performance of shale samples is better, with the average adsorption capacity of 4.38 ml/g. The Langmuir model fits well with the adsorption curves. The adsorption capacity of shale samples increases as total organic carbon (TOC) increases and temperature decreases. The adsorption potential theory was used to explain the influence of shale adsorption factors.